Theory of mind, birth order, and siblings among preschool children. - Farhadian, Mokhtar; Abdullah, Rohani; Mansor, Mariani; Redzuan, Ma’arof; Kumar, Vijay; Gazanizad, Neda (EuroJournals Publishing, Inc., 2010)
This research investigated whether the number of siblings in the family facilitatesthe development of theory of mind (ToM) in preschool children. A battery of tests was administered to measure the ToM and verbal ability of one hundred and sixty three 3.6 to5.6 year-old children. No significant difference was found between ToM and siblings. Incontrast, a significant difference was found between ToM and birth order. Additionally, onundertaking a hierarchical multiple regression analysis, it was found that, over and aboveage and verbal ability, a significant contribution for birth order to ToM development wasobserved.